Meteor Head Echo Analyses From Concurrent Radar Observations at AMISR Resolute Bay, Jicamarca, and Millstone Hill. Issue 10 (6th October 2022) - Hedges, T.; Lee, N.; Elschot, S.
Abstract: On 10 and 11 October 2019, high‐power radar observations were performed simultaneously for 8 hours at Resolute Bay Incoherent Scatter North (RISR‐N), Jicamarca Radio Observatory (JRO), and Millstone Hill Observatory (MHO). The concurrent observations eliminate diurnal, seasonal, and space weather biases in the meteor head echo populations and elucidate relative sensitivities of each facility and configuration. Each facility observed thousands of head echoes, with JRO observing tens of thousands. An inter‐pulse phase matching technique employs Doppler shifts to determine head echo range rates (velocity component along radar beam) with order‐of‐magnitude greater accuracy versus measuring the Doppler shift at individual pulses, and this technique yields accurate range rates and decelerations for a subset of the head echo population at each facility. Because RISR‐N is at high latitude and points away from the ecliptic plane, it does not observe head echoes with range rates faster than 55 km/s, although its head echo population demonstrates a bias toward larger and faster head echoes. At JRO near the equator, a larger spread of range rates is observed. MHO observes a large spread of range rates at mid‐latitude despite its comparable frequency to RISR‐N, but this occurs because its beam was pointed at a 45° elevation angle unlike RISR‐N and JRO which were pointed near‐zenith. A trend of greater decelerations at lower altitudes is observed at RISR‐N and JRO, with decelerations of up to 60 km/s 2, but high‐deceleration events of up to 1, 000 km/s 2 previously observed in head echo studies are not observed. Key Points: Sensitivity to head echoes of three high‐power radar instruments across varying latitudes are studied via concurrent observations An inter‐pulse phase‐matching technique enables accurate range deceleration measurements When radar beam is zenith‐pointing, higher decelerations are observed at lower altitudes, reflecting the atmospheric neutral density profile